Unveiling the hidden diversity: the second species of Wenchengia (Lamiaceae) discovered from a dry mountaintop meadow of Hainan Island, China - Si-Cheng Xu; Jin-Fei Xiao; Chun-Lei Xiang; Bo Li (PhytoKeys, 2025)
Wenchengia wui, a remarkable new species of Wenchengia endemic to a dry mountaintop meadow of Sanya City, Hainan Province, southern China, is described and illustrated. The new species is readily distinguished from the only other extant species, W. alternifolia, by its opposite phyllotaxy, oblong-ovate leaves with rounded to slightly truncate bases, shallowly funnelform calyces with spreading lips, and 8-ribbed nutlets, as well as its unique habitat preference. The new species is categorized as Critically Endangered (CR) according to the IUCN Red List criteria, based on its limited distribution, specialized habitat, and small population size. Detailed information on its distribution, habitat, diagnostic characteristics, and a comprehensive morphological description are provided. The discovery of this new species offers valuable insights into the evolutionary history and conservation strategies of Wenchengia.